CRISPR/Cas9-Mediated BocPDSs Gene Editing in Chinese Kale Using the Endogenous tRNA-Processing System - Yudan Wang; Rahat Sharif; Guangguang Li; Guoju Chen; Changming Chen (Horticulturae)
Chinese kale is a native vegetable from the Brassicaceae family that is grown extensively in Southeast Asia and Southern China. Its low genetic transformation and gene editing efficiency hinder gene function research and molecular biology in Chinese kale. CRISPR/Cas9 is a useful tool for plant genome research due to its rapid development and optimization. This study targeted BocPDSs, (BocPDS1, BocPDS2) to establish an effective CRISPR/Cas9 system in Chinese kale. A tandemly arranged tRNA-sgRNA construct was used to express numerous sgRNAs to induce BocPDS1 and BocPDS2 double and single mutations, with a mutation rate of 61.11%. As predicted, several mutant plants showed an albino phenotype with a harbored mutation in an exon and intron region, highlighting the relevance of the intron. The presence of mutations in the intron region suggests that the cleavage process in Chinese kale, utilizing CRISPR/Cas9 shows a preference for AT-rich regions. The distinct and somewhat redundant functions of BocPDS1 and BocPDS2 are demonstrated by the complete albino phenotype of the double mutants and the mosaic albino phenotype of the individual BocPDS1 and BocPDS2 mutants. Specific gene editing modes, including base deletion, base substitution, and base insertion, were identified in the sequence of the target gene. Among them, short nucleotide insertions were the most common type of insertion, with base insertions having the highest frequency (61.54%). Furthermore, no instances of off-target gene editing were detected. The current work demonstrated that the CRISPR/Cas9 gene editing system, which relies on endogenous tRNA processing, can effectively induce mutagenesis in Chinese kale. This finding establishes a theoretical basis and technical backbone for the more effective implementation of CRISPR/Cas9 gene-editing technology in Chinese kale and Brassica plants.